2022
DOI: 10.3390/polym14235100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Degradation Performance of Seven Different Choline Chloride-Based DES Systems on Alkaline Lignin

Abstract: Lignin is a natural polymer second only to cellulose in natural reserves, whose structure is an aromatic macromolecule composed of benzene propane monomers connected by chemical bonds such as carbon–carbon bonds and ether bonds. Degradation is one of the ways to achieve the high-value conversion of lignin, among which the heating degradation of lignin by deep eutectic solvent (DES) can be an excellent green degradation method. In this study, choline chloride (CC) was used as the hydrogen bond acceptor, and ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As a result, ChCl : PTSA produced larger, whereas ChCl : Gly produced a smaller content of phenolic hydroxyl groups. 157 By employing three distinct DESs, namely ChCl : OA (1 : 1), ChCl : LA (1 : 1), and ChCl : FA (1 : 2), under microwave irradiation at varied temperatures and times, Muley et al 158 were able to deconstruct biomass and depolymerize kraft lignin. According to the results, the maximum lignin yields were obtained with ChCl : FA at 150 °C for 15 min and ChCl : OA DES at 130 °C.…”
Section: Deep Eutectic Solvents (Dess)mentioning
confidence: 99%
“…As a result, ChCl : PTSA produced larger, whereas ChCl : Gly produced a smaller content of phenolic hydroxyl groups. 157 By employing three distinct DESs, namely ChCl : OA (1 : 1), ChCl : LA (1 : 1), and ChCl : FA (1 : 2), under microwave irradiation at varied temperatures and times, Muley et al 158 were able to deconstruct biomass and depolymerize kraft lignin. According to the results, the maximum lignin yields were obtained with ChCl : FA at 150 °C for 15 min and ChCl : OA DES at 130 °C.…”
Section: Deep Eutectic Solvents (Dess)mentioning
confidence: 99%
“…They are composed of different molar ratios of a hydrogen bond acceptor (such as choline chloride) and a hydrogen bond donor (like lactic acid, urea, ethylene glycol, etc.) [119,120]. The DES pretreatment can increase both the digestibility and solubility of lignocellulose and reduce its resistance to enzymatic digestion; it can also selectively break ether bonds to separate lignins and celluloses, thus deconstructing plant cell walls effectively [121].…”
Section: Solvent Pretreamentmentioning
confidence: 99%
“…The intense absorption band at 3405 cm −1 is caused by the O-H stretching vibration of the OH group in the product, which is where we need to focus our attention, and the unique peak signal of the symmetric and asymmetric vibration of the different peaks C-H at 2930 cm −1 . The spectrum exhibits a weaker peak at 1705 cm −1 , suggesting that the DES treatment process may have resulted in more β-O-4′ bond cleavage [23,24]. Consequently, the relatively…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…The product obtained from laccase treatment had the highest phenolic hydroxyl content and lower molecular weight, and showed the exceptional antioxidant activity (IC 50 = 28.8 µg/mL), even compared to the commercially available antioxidants BHT (3,5-di-tert-butyl-4-hydroxytoluene, IC 50 = 38.2 µg/mL) and BHA (3-tert-butyl-4-hydroxyanisole, IC 50 = 56.3 µg/mL). Our group also studied the effect of deep eutectic solvents (DES) on the degradation of AL in the early stage and found that the acidic choline chloride-based DES system was effective in obtaining lignin monomers, with more phenolic hydroxyl groups, lower molecular weight and more homogeneity, which have good prospects for improving their antioxidant properties [23,24].…”
Section: Introductionmentioning
confidence: 99%